UPAYA PENINGKATAN KEMAMPUAN DASAR MENGAJAR MAHASISWA BIOLOGI MELALUI MODELING DIPADU STUDENT INVESTATION BERBASIS LESSON STUDY - Samuel Agus Triyanto (Jurnal Pendidikan Biologi, 2015)
College student offering A-A of Biology Education 2013 University of Malang force has a problem in rhetoric, seen from the use of language which is less effective at teaching basic skills performance. These problems, if left unchecked will have an impact on the difficulty of the increase in basic teaching skills. This study aims to improve basic teaching skills in materials explaining skills and open lessons. This research is a classroom action research (PTK) based Lesson Study. Data basic teaching skills gained through observation and documentation. Data were analyzed by using qualitative descriptive analysis. The results showed that the basic teaching skills have increased, especially in explaining the skill and open skill lessons. Based on the results of this study concluded that the application of modeling combined with Student Investation can improve basic teaching skills of students on the material to explain the skills and open lessons.Keywords : Modeling, Student Investation, Lesson Study, Teaching Basic Capabilities